Socio-cognitive factors underlying child abuse and neglect: the role of parental attributions - Camilo, Cláudia Sofia Dinis (2020)
Socio-cognitive models explaining maladaptive parenting have been examining the cognitive information processing mechanisms in determining parental behavior towards children. Among different cognitions, parental attributions about child’s behavior seem to have an important role to child maltreatment. However, little research has been conducted with in neglectful parents and the different patterns of parental attributions that are associated with child abuse and child neglect respectively are still underexplained. In order to explore parental attributions associated with (self and professionals-reported) abusive and neglectful parental practices, 218 mothers participated in this study (half of them referred to the child protection services). Moreover, the effect of transgression-mitigating information, and the moderation effect of maternal intellectual functioning and socioeconomic status were examined. The results suggested that mothers with higher scores on child abuse and neglect report more internal, global and stable attributions about the child’s behavior, and feel less in control of the child’s behavior. However, different attributional dimensions were found to be associated with abuse and with neglect respectively, and the effect of mitigating information also seems to be higher for child neglect. Surprisingly, the moderating role of intellectual functioning for child neglect indicated that higher neglect scores were associated with more internal and global attributions in mothers with higher levels of intellectual functioning. This work presents a contribution to the still emerging research about parental cognitions in the context of child maltreatment. The theoretical and practical implications of these findings are discussed.